Performansi Mesin Refrigerasi Siklus Kompresi Uap Pada Massa 60 Gram Menggunakan Refrigeran Hidrokarbon - Nurul Deswita; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
An energy saving and sustainable environmental become an attention of the world nowdays. Replacement of halocarbon refrigerant to hydrocarbon give positive impact to the environment because hydrocarbon is friendly refrigeran for environment with low GWP (Global Warming Potensial and zero ODP (Ozon Depleting Potensial). With the replacement refrigerant, it will cause a change performance on refrigeration machine. This study was conducted to determine the effect of hydrocarbon refrigerants with mass amounts of 60 grams on the performance refrigeration machine. The method used in this study was an experimental method to perform the replacement of halocarbons into a hydrocarbon refrigerant with mass amounts of hydrocarbon refrigerants of 60 grams. The results of the study of refrigerant hydrocarbon with mass amounts of 60 grams was found that the required electrical power for compressor of 0.14 kW, power of cooling of 0.73 kW, the heating power of 0.94 kW, and Coefficient Of Performance of 5.21.Keywords: Refrigeration Machine, Refrigerant Mass, Performance, Hydrocarbon Refrigerants